RASIO LEGIS PENGATURAN USIA PERKAWINAN MENURUT UNDANG UNDANG PERKAWINAN DARI SUDUT PANDANG HUKUM NORMATIF - Berton Armandes Pakpahan (I’tiqadiah: Jurnal Hukum dan Ilmu-ilmu Kesyariahan, 2024)
Marriage is a bond between two human beings in their lives which is very important. Once the importance of marriage, it is not surprising that the world's religions regulate marriage, even the customs of society and state institutions do not lag behind regulating the marriage that prevails among the people.  The law regulates marriages, one of which is the minimum age of marriage contained in article 7 paragraph (1) which states that, "Marriage is only permitted if the male has reached the age of 19 (nineteen) years and the woman has reached the age of 16 (sixteen) ) year "